Schizophrenic Language and Behaviour Analysis of the Main Character in Do Androids Dream of Electric Sheep? Novel - Lina, Ester; Rahayu, Famala Eka Sanhadi (Fakultas Ilmu Budaya Universitas Mulawarman, 2025)
Humans should be able to convey their thoughts and feelings to one another with minimal problems. However, when an individual’s brain is affected by a condition such as schizophrenia, effective communication can become challenging due to disrupted cognition, leading to what could be considered a language disorder. This concept was portrayed through the character John R. Isidore, a main character in Philip K. Dick's novel Do Androids Dream of Electric Sheep? The researcher was intrigued to study how Isidore exhibited behaviours associated with schizophrenia and to identify the language disorders he experienced within the context of post-apocalyptic San Francisco. To explore this, the researcher first examined Isidore’s thoughts and actions as described by the author, employing the psychopathology of schizophrenia framework established by Lindenmayer & Khan (2012). The researcher then analyzed the language disorders present in Isidore's character using the thought and language index (TLI) instrument. The analysis revealed that Isidore displayed a comprehensive range of symptoms across the schizophrenia spectrum, with a notable prominence of positive symptoms. Moreover, Isidore manifested all eight language disorders associated with schizophrenia, with the most pronounced of these disorders was the perseveration of ideas. Keywords: schizophrenia, symptoms, language disorders, Do Androids Dream of Electric Sheep?